Constitutional Judiciary in Maghreb Countries: The Algerian and Tunisian Constitutional Courts as Models :Tradition or Transformation in Constitutional Justice? - Allouache , Farid; Benmechri , Abdelhalim; MOHAMED , DJAGHAM (Journal of Ecohumanism, 2026)
This article aims to shed light on the most important constitutional bodies tasked with ensuring and safeguarding the protection and respect of the constitutional legal rule. It is observed from the outset that the spread of judicial review over the constitutionality of laws is accompanied by a decline in political oversight, which may give the impression that judicial oversight is better than political oversight. This prompted us to conduct this study, through which we highlight the two most important constitutional courts in the Maghreb, namely the Algerian Constitutional Court and its Tunisian counterpart, by addressing the founding texts of these courts, as well as their composition and the powers granted to them, in order to confirm or deny the ability of these bodies to perform their assigned role.